2015
DOI: 10.1136/bmjopen-2015-008164
|View full text |Cite
|
Sign up to set email alerts
|

Potential economic consequences of a cardioprotective agent for patients with myocardial infarction: modelling study

Abstract: ObjectiveTo investigate the cost-effectiveness of a hypothetical cardioprotective agent used to reduce infarct size in patients undergoing percutaneous coronary intervention (PCI) after anterior ST-elevation myocardial infarction.MethodsDesign: A cost-utility analysis using a Markov model. Setting: The National Health Service in the UK. Patients: Patients undergoing PCI after anterior ST-elevation myocardial infarction. Interventions: A cardioprotective agent given at the time of reperfusion compared to no car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Although, in recent years, there have been several studies on ischemic conditioning (pre- and post-conditioning), they have been disappointing in their clinical application [ 145 ]. Because of this, other ways to achieve cardioprotection have been studied, and a cost-effective study has established the positive economic consequences of the use of a cardioprotective therapy in patients with AMI involving endogenous cardioprotection strategies, beta-blocker therapy, or even mitochondria-targeted cardioprotection strategies [ 11 , 145 , 146 ], which makes it a very striking strategy not only for its effects at the tissue level. According to Davidson et al, a multitarget cardioprotective therapy is defined as the additive or synergistic cardioprotective effects of multiple agents or interventions directed to distinct targets [ 11 ] and that, in the future, this option should be considered as a parallel treatment to the restoration of blood flow after ischemia.…”
Section: Towards a Potential Synergistic Cardioprotection Achieved By Combined Antioxidantsmentioning
confidence: 99%
“…Although, in recent years, there have been several studies on ischemic conditioning (pre- and post-conditioning), they have been disappointing in their clinical application [ 145 ]. Because of this, other ways to achieve cardioprotection have been studied, and a cost-effective study has established the positive economic consequences of the use of a cardioprotective therapy in patients with AMI involving endogenous cardioprotection strategies, beta-blocker therapy, or even mitochondria-targeted cardioprotection strategies [ 11 , 145 , 146 ], which makes it a very striking strategy not only for its effects at the tissue level. According to Davidson et al, a multitarget cardioprotective therapy is defined as the additive or synergistic cardioprotective effects of multiple agents or interventions directed to distinct targets [ 11 ] and that, in the future, this option should be considered as a parallel treatment to the restoration of blood flow after ischemia.…”
Section: Towards a Potential Synergistic Cardioprotection Achieved By Combined Antioxidantsmentioning
confidence: 99%
“…A hypothetical analysis determined that any cardioprotective agent that reduces the risk of HF and mortality after PCI is likely to be cost-effective; however, the likelihood will depend on the price of the agent, age of the study cohort, and the relative risk of HF after PCI. 12 To be cost-effective, the authors calculated that the maximum cost of the therapy should be less than £2500 and the reduction in HF incidence and mortality should be at least 20%. 12 These values are consistent with our data.…”
Section: Discussionmentioning
confidence: 99%
“…12 To be cost-effective, the authors calculated that the maximum cost of the therapy should be less than £2500 and the reduction in HF incidence and mortality should be at least 20%. 12 These values are consistent with our data. Specifically, we showed that if MACE reduction found in our study with sodium nitrite is replicated in a larger study, then the therapy could cost up to £2006 and remain cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling and simulation (M&S) has been often used in cost-effective analysis for decision-making. 5,11,12) A Markov process model 13,14) has been used for modeling changes in disease conditions in patients, and a typical index such as the incremental cost-effective ratio (ICER) 15) has been used for this purpose. In a Markov model, transition probabilities are estimated from hazard rates of progression free survival (PFS) or overall survival (OS), and a time course profile of PFS or OS is not considered.…”
Section: )mentioning
confidence: 99%